Why the kinked demand curve may still be useful. Issue 4 (4th July 2021) - Galles, Gary M.; Sexton, Robert L.
Abstract: Unlike the common interpretation and consequent general rejection of the kinked demand curve, J.M. Clark developed a different, and more useful, interpretation of the kinked demand curve. While his approach was not generally understood, for reasons we will discuss (including the fact that his discussion of related issues was scattered among multiple books and articles, many of which primarily focussed on other issues), Clark's approach to the kinked demand curve offers valuable insights into typically overlooked properties of imperfect, price-quoting markets, as opposed to the standard implicit assumption of perfect markets.